Origin of the Shangla Blueschist, Swat Himalaya, Pakistan - Shams, P.A. (Journal of Himalayan Earth Sciences, 1980)
Chemical analysis of two metasedimentary and one meta-igneous-type blueschist rocks from Swat suggest that the former type is hypersodic as compared with many of the world occurrences. The blue amphibole is crosstie of appropriate chemical composition. The rocks are believed to be of metasomatic origin, having sulfered soda activity of pore fluids. A yet younger phase of soda activity originated from sepentinisation of the Alpurai ultramafic mass and was responsible for growth of the albite prophyroblasts that contain helicytic trails of the blue amphibole. The blueschist zone is taken to mark a typical fossil trenchplate subduction suture in terms of the ories of global tectonics. Radiometric age of muscovite from a metasedimentary blueschist type is 84+-1.7 m.y. or upper Coniacian which compares suitable with other ages obtained from the region. The presence of this early Alpine subduction zone of the swat Himalaya is taken to represent the continuation of the Indus Suture Line.